Analisis Nilai-Nilai Toleransi Dalam Buku Ajar Sejarah Kebudayaan Islam MI - Arlina A; Restu Audy Azhari; Afifah Salsabila; Melati Maharani; Nur Asiah Hasibuan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
One of the key educational tools in the campaign to promote tolerance's ideals is the text book. This study was carried out to determine the tolerance-promoting principles found in the history of Islamic culture textbooks used at Madrasah Ibtidaiyah as well as the principles that still need to be improved upon in those texts. This kind of investigation is done at libraries. The findings of this study demonstrate that the ideals of tolerance included in the SKI Madrasah Ibtidaiyah (MI) textbook include respecting one another, fostering togetherness, achieving wellbeing, and being mindful of one another's views toward others. These tolerance-promoting principles must be properly grasped.